(untitled) (Journal of Nepal Physical Society, 2021)
Solar radiation data are of great significance for energy harvesting. This paper’s main objective is to study clearness index of atmosphere over Biratnagar (latitude: 26.45° N, longitude: 87.27° E, altitude: 72 m a. s. l.), an eastern city of Nepal. Daily global solar radiation data are derived by using CMP6 pyranometer for one year period (2015). The monthly, annual and seasonal variations of global solar radiation, clearness index and visibility were analyzed. The annual average of global solar radiation (GSR), clearness index (KT) and visibility indices are found to be 11.37 ± 3.76 MJ/m2 /day, 0.37 ± 0.15 and 7.06 ± 5.56 km are respectively. In the study period, number of clear days (KT >0.65) and number of cloudy days (KT <0.34) are found to be 26 and 172 respectively. Study of clearness index of atmosphere and its dependence on meteorological parameters (such as maximum temperature, minimum temperature, rainfall, relative humidity, total ozone column and dew point) are used on agriculture, hydrology, and climate change. Finding of GSR and visibility helps for energy harvesting and aviation.